Biomimetic Dual-Iron-Site Single-Atom Nanozymes for N 2 -Selective Electrocatalytic Denitrification - Song, Wanchao; Liu, Guoshuai; Zou, Hua; Yao, Yuan; You, Shijie (Environmental science & technology, 2025)
Electrocatalytic denitrification (ECDN) for the reduction of NO to N offers an effective and environmentally benign method for removing nitrogen from wastewater, but challenges remain for poor N selectivity. To address this issue, this study reports a dual-iron-site single-atom nanozyme (SAN, FePc@FeNOC) electrocatalyst, resembling the natural cytochrome c-dependent nitric oxide reductase (cNOR). The FePc@FeNOC electrocatalyst exhibits a NO removal efficiency as high as 96.1%, accounting for N selectivity of 93.3% and Faradaic efficiency of 82.8% at a reaction time of 10 h. The theoretical results reveal that the potential-determining step of ECDN to N is more thermodynamically favorable than that to NH by FePc@FeNOC, as indicated by the lower free energy barrier for *NO to *N O (0.82 eV) compared with that for *NO to *NOH (0.87 eV). The *N O intermediate demonstrates enhanced charge separation compared with *NOH. The charge redistribution strengthens the electrostatic coupling between FePc@FeNOC and *N O , which not only stabilizes the intermediate structure but also creates a thermodynamic driving force for N formation. We further demonstrate that the superior N -selectivity (90%) of FePc@FeNOC can offer a promising electrocatalyst for removing nitrogen from realistic photovoltaic wastewater with a low energy consumption of 9.8 kWh kgN . This work provides a proof-in-concept demonstration of mimicking cNOR toward the sustainable treatment of nitrate-contaminated wastewater.